75 Years : the very best of Life - Sullivan, Robert, 1953- (New York, New York : Life Books, 2011)
Presents a selection of the best photographs published in "Life" magazine and by Life Books, including war pictures, candid shots of celebrities, nature scenes, and views of social and cultural concerns, along with a facsimile of the first issue.
"To see the world" -- 10 places in our world -- 4 pieces of paradise -- 8 relations -- "To eyewitness great events" -- 17 from the battlefield -- 8 with the right stuff -- 8 that changed the world -- 5 cover stories that vanished -- 6 heroes -- LIFE's heroes -- 4 villains -- 17 great reads -- "To watch the faces of the poor and the gestures of the proud" -- 6 faces of the poor -- 3 found by LIFE -- 7 gestures of the proud -- "Things hidden behind walls and within rooms" -- 25 candid moments -- 3 of real people -- 12 backstage on the world stage -- "The women that men love and many children" -- 15 of LIFE's sexiest -- LIFE's best friends -- 5 best kids photos -- 2 best kisses -- "To see and be amazed" -- 5 wows -- 6 from the arena -- 7 scariest -- 2 from out there -- The covers -- Back to the future -- LIFE.com and "Never before seen!" photography -- Back to the beginning -- The Fort Peck Dam story we never told.
Incluye un facsímil de la primera edición, completo y de tamaño completo, de fecha 23 de Nov., 1936.
Keywords: FOTOGRAFIA ARTISTICA; DISEÑO DE REVISTAS; REVISTAS ESTADOUNIDENSES; REPORTAJES FOTOGRAFICOS; PERIODISMO GRAFICO; ESTADOS UNIDOS -- HISTORIA -- REVISTAS